Plasmids and antibiotic resistance in Aeromonas hydrophila isolated in Malaysia from healthy and diseased fish - Ansary, A.; Haneef, R.M.; Torres, J.L.; Yadav, M. (Wiley Blackwell, 1992)
Thirty‐four A. hydrophila strains isolated from various fish species and several geographical locations in Malaysia were examined for their antibiotic resistance pattern and plasmid carriage. All strains were found to possess multiple resisitance, most commonly to ampicillin and carbenicillin. Six different antibiogroups representing 18 different antibiotic patterns were obtained. There were no differences in the resistance patterns of A. hydrophila isolates from healthy and diseased fish with ulcerative syndrome. Rifampicin was found to be the most active antibiotic against these strains. Isolation of plasmid DNA have a plasmid occurrence rate of only 14·7%. The molecular sizes of these plasmids ranged from 2·6 to 6Mda. Multiple carriage of plasmid is more likely with strains having three of four plasmids.